PENGARUH LOCUS OF CONTROL DAN KECERDASAN EMOSIONAL TERHADAP KEMAMPUAN MEMECAHKAN MASALAH PADA REMAJA DESA PERCUT KECAMATAN PERCUT SEI TUAN - Syarifah Syarifah; Nefi Darmayanti (Analitika: Jurnal Magister Psikologi UMA, 2010)
This research was aimed at analyzing the effect of locus of control and emotional quotient on problem solving skills in adolescent of village Percut Kecamatan Percut Sei Tuan. In 1231 populations of adolescents 16 -18, only 160 sampled respondents and finally as a sample to analyze the hypothesis counted 136 subjects. This is because the 15 questionnaries not return and 9 subjects didn’t fill the questionnaries completely.To analyze the hypothesis about effect of X1 and X2 variable to Y variable we use Multiple Regression analysis.  The effect of X1 and X2 variable on Y variable can be seen from Coefficient Determination (R.Square) = 0,29, indicate that 21,9% of problem solving skills is influenced by locus of control and emotional quotient. The rest, 23,2 % was cause by other variables from out side this research.Coeffient Correlation between X1 variable and  Y variable is 0,388. Score of r is bigger than r table, show that significant and positive influences are 0,388 between locus of control and problem solvings skills. Coeffient Correlation between X2 variable and  Y variable is 0,427, bigger than r table too in significancy level 5%,  that significant and positive effect between emotional quotient and problem solvings skills. r table to N=136 on believing interval 95% or significancy level 5% is 0,159. (Arikunto, 1998: 366)